Designing Beam Capture Settings For Solar Power Plants - Muhammad Ridwan; Arief Suardi N.C (Publikasi Indonesia, 2024)
Solar Power Plant (PLTS) absorbs solar energy and is adjusted to the change in circulation from 06.00 in the morning to 17.00 in the afternoon. This requires adjustment to the installation of a solar power plant so that energy capture can be optimal; this adjustment uses a sunlight capture tool called Suntracker. The main tools are in the form of movers, timers and work steps that can be dragged. Based on the testing results and discussion of the overall design of solar trackers, namely. The highest current measurement results in stationary solar cells (static) occur at 11.00 WIB, which is 0.23 A. The highest current measurement results on solar trackers also occur at 10.00 WIB, 0.25 A. The highest voltage measurement in stationary solar cells occurs at 10.00 WIB, which is 14.2 volts. Moreover, the highest voltage measurement results on the solar tracker occurred at 10.00 WIB, which is 20.3 volts.